Brand Experience and WOM: The Mediating Effects of Brand Love, Brand Image, and Brand Loyalty - Nikodemus Hans Setiadi Wijaya; Bernadeta Agustin Anjasari (AIBPM Publisher, 2022)
In marketing, word of mouth (WOM, whether positive or negative, can have a significant impact on overall marketing success because it influences the reputation of the company and the product brand. To foster positive WOM, marketers should manage the consumer experience when consuming a product brand. This study applies brand love, brand image, and brand loyalty to the effect of brand experience on WOM. Brand love, brand image and brand loyalty are posited as mediators. The present study employed consumers of a pharmaceutical brand originating from Japan. The online survey gathered 293 data that could be used for analysis. By using the two types of positive WOM (face-to-face WOM and electronic WOM, later abbreviated as f-WOM and e-WOM) this study revealed that the brand experience was positively associated with e-WOM and f-WOM. Brand experience was associated with e-WOM through brand love, brand image and brand loyalty. In addition, brand experience was associated with f-WOM through brand love, brand image and brand loyalty. The study offers important information to marketers. Through brand property management, organizations would scan positive WOM from their consumers, in turn it may be a good spontaneous promotion at their brands.